2020
DOI: 10.1016/j.childyouth.2020.105578
|View full text |Cite
|
Sign up to set email alerts
|

College students’ experience of emergency remote teaching due to COVID-19

Abstract: Highlights College students’ experiences of emergency remote teaching due to COVID19. Results revealed advantages, disadvantages, and desired improvements. The need for further development for a successful learning experience is demonstrated. Specific suggestions for such developments are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
231
4
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(273 citation statements)
references
References 13 publications
22
231
4
16
Order By: Relevance
“…Students’ responses make it clear that opportunities for students to engage with their peers and the instructor need to be built into both synchronous and asynchronous instruction ( Wilcox & Vignat, 2020 ). Shim and Song (2020) found that the absence of interaction between students and professors reduced their satisfaction with ERT. Bai and colleagues ( 2020 ) found that most students preferred the physical classroom because of the absence of interaction in an online environment.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Students’ responses make it clear that opportunities for students to engage with their peers and the instructor need to be built into both synchronous and asynchronous instruction ( Wilcox & Vignat, 2020 ). Shim and Song (2020) found that the absence of interaction between students and professors reduced their satisfaction with ERT. Bai and colleagues ( 2020 ) found that most students preferred the physical classroom because of the absence of interaction in an online environment.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Many studies address the issue of technology challenges, particularly in the context of students who do not have adequate access to the internet, computers/printers, or lack technological skill to negotiate the online environment (e.g., Aboagye et al., 2020 ; Shim & Song, 2020 ; Trust & Whalen, 2020 ; Wiltse et al., 2020 ; Mseleku, 2020) . Gillis and Krull (2020) discovered that internet and technology barriers were widespread.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies regarding online learning across higher education have been conducted, that have enhanced both the understanding and practical implications of adopting different modes of online learning, such as blended, asynchronous, and synchronous learning [15]. To determine the success of e-learning in higher education student satisfaction is an important indicator to determine performance [2,5,[8][9][10][11][12][13][14][15][16]. Duque (2013) proposed a framework for evaluating higher education performance with students' satisfaction, perceived learning outcomes, and dropout intentions, and found that dropout intentions were strongly and negatively associated with student satisfaction [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Countries and cities continue to be locked down to promote social distancing and prevent excessive gatherings, controlling the further spread of COVID-19 [1]. Due to the unpredictable length of this pandemic, most education institutes have adopted emergency remote learning (ERL) via online learning platforms, to replace most, if not all, face-to-face theoretical and practical lessons [2][3][4][5]. Even programs traditionally taught in person have rapidly shifted to online learning, to fulfill education obligations and…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worth considering the tools to ensure networking implementation in practice. Scholars agree tat networking is crucial during Covid-19 caused remote education (Shim, Lee, 2020). However, the author's personal experience reveals that much depends on internal readiness of the group members to the respective activities as part of the learning process and not just entertainment.…”
Section: Students' Networkingmentioning
confidence: 98%